Broadband (NIR-Vis-UV) photoresponse of annealed SnSe films and effective oxidation passivation using Si protective layer. (September 2022) - Kumar, Manoj; Rani, Sanju; Kumar, Ashish; Tawale, Jai; Srivastava, Ritu; Singh, Bhanu Pratap; Pathak, Saurabh; Wang, Xu; Singh, V.N.
Highlights: SnSe film's thermal and chemical stability at 200, 250, and 300 °C in the open air is studied. Samples annealed at 300 °C showed a broadband spectral response due to SnSe, SnSe2, and SnO2 phases. The formation of three layers viz SnSe, SnSe2, and SnO2 can be used for solar cells. Deposition of Si as a protective layer on the SnSe for improved oxidation stability up to 250 °C. Abstract: Tin selenide is a versatile material with superior thermoelectric properties and can compete for optoelectronics, gas sensing, etc. As the actual application of the device depends upon the stability of the material under practical conditions (like for thermoelectric application, the material must be stable up to the defined temperature at which ZT is maximum). This paper reports the material's systematic thermal and chemical stability for feasible, practical applications in optoelectronic and thermoelectric aspects. SnSe film was deposited on the soda-lime glass substrate using thermal evaporation. Annealing was carried out at different temperatures (200, 250, and 300 °C) for one hour in open-air conditions. With the increase in the annealing temperature, part of the SnSe phase was initially changed to the SnSe2 phase, and a tin dioxide layer was formed (confirmed by Raman spectroscopy). A blue shift in the direct bandgap (from 1.35 eV, for pure SnSe to 1.84 eV, for 300 °C annealed SnSe) has been observed with an increase in annealing temperature. Atomic force and scanning electron microscopic studies have been carried out. Samples annealed at 300 °C showed a broadband spectral response due to crystalline SnSe, SnSe2, and SnO2 phases. Also, the formation of three consecutive layers viz SnSe, SnSe2, and SnO2 can be used for solar cell applications. Further, deposition of Si as a protective layer on the SnSe for improved oxidation stability has been carried out, which resisted the oxidation up to 250 °C. Graphical abstract: Image, graphical abstract